The Students’ Skill in Performing A Speech in SMA Negeri 6 Pinrang - Haslinda Haslinda; Mujahidah Mujahidah; Nurhamdah Nurhamdah (LETS: Journal of Linguistics and English Teaching Studies, 2021)
The aims from this research are to know how is students’ skill in performing a speech, and to know the students’ deprivation in performing a speech. This research is mix method design to answer the problem of this thesis. The research took place at SMA N 6 Pinrang. The population was the students from eleventh grade, the sample of this research were 34 students who are from class XI MIPA 1 by used purposive sampling technique. The researcher used test and interview as instrument for this research. The speech performance used manuscript speech delivery method. The results of this research find that the students’ skill in performing speech are not fully fill up with the criteria of assessment, where the mean score from the performance is 189.79. Additionally, in analyzing the interview, the researchers conclude that there are some deprivations when the students perform their speech, the factors that been found over the interview were the use of English as a language used it selves in performing a speech. Moreover, the use of vocal variety and physical movement also mentioned with the students as their deprivation in performing a speech.